Using Implementation Science to Further the Adoption and Implementation of Advance Care Planning in Rural Primary Care. Issue 1 (23rd September 2019) - Nelson‐Brantley, Heather; Buller, Carol; Befort, Christie; Ellerbeck, Edward; Shifter, Ariel; Ellis, Shellie
Abstract: Purpose: To analyze the literature on advance care planning (ACP) in primary care through the lens of implementation science, with a focus on implications for rural settings. Design: Scoping review of the literature. Methods: The Cumulative Index of Nursing and Allied Health Literature (CINAHL), Medline, PsycINFO, and the Psychology and Behavioral Sciences Collection databases were searched for studies related to ACP adoption and implementation in primary care. The Theoretical Domains Framework was used to map the literature to 14 determinants that serve as barriers or facilitators to ACP. The Conceptual Model of Evidence‐Based Practice Implementation in Public Service Sectors was used to analyze the stage of implementation for each of the included studies. Findings: Four steps to ACP were specified: identification, conversation, documentation, and follow‐up. Determinants were identified for each step, but studies largely focused on the conversation step. Professional role and identity, environmental context and resources, and emotion were the most frequently cited determinants in initiating conversations. The identification step was largely determined by behavioral regulation. For documenting ACP, environmental context and resource determinants were most prevalent. In the few studies that addressed follow‐up, providers expressed a desire for electronic reminders as a behavioral regulator to follow‐up. Conclusions: While ACP has been shown to have patient, family, and societal benefits, its uptake in primary care has been minimal. Because ACP is a complex process that is highly context dependent, implementation science is critical to inform its successful adoption and implementation. Smaller healthcare networks, adaptable professional roles, trusted relationships, and tight‐knit community might be important facilitators of ACP in rural primary care. Clinical Relevance: Findings from this study can be used to accelerate ACP implementation in rural primary care.